1987
DOI: 10.1042/bj2480123
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of three peptides derived from prosomatostatin [prosomatostatin-(1–63)-, -(65–76)- and -(79–92)-peptides] in a human pancreatic tumour

Abstract: By using only reverse-phase h.p.l.c., three fragments of prosomatostatin were isolated from an extract of a human pancreatic neuroendocrine tumour that produced somatostatin, vasoactive intestinal polypeptide and gastrin-releasing peptide. The amino acid composition of the peptides indicated that they represented prosomatostatin-(1-63)-peptide, prosomatostain-(65-76)-peptide and prosomatostatin-(79-92)-peptide (somatostatin-14). The identity of prosomatostatin-(1-63)-peptide was confirmed by characterization o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Human prosomatostatin is a protein build from 92 AAs, and is proteolytically cleaved at the arginine–lysine and arginine processing sites. Partial micro-sequencing of prosomatostatin-(1-63)-peptide demonstrated that the site of the cleavage of the signal peptide was located at the Gly24-Ala25 bond [ 94 ].…”
Section: The Srif System—general Commentsmentioning
confidence: 99%
“…Human prosomatostatin is a protein build from 92 AAs, and is proteolytically cleaved at the arginine–lysine and arginine processing sites. Partial micro-sequencing of prosomatostatin-(1-63)-peptide demonstrated that the site of the cleavage of the signal peptide was located at the Gly24-Ala25 bond [ 94 ].…”
Section: The Srif System—general Commentsmentioning
confidence: 99%
“…Structural analysis Amino acid compositions were determined by using a Durrum automatic analyser as described previously (Conlon et al, 1987). Cysteine and tryptophan residues were not measured.…”
Section: K 21mentioning
confidence: 99%
“…Amino acid composition was determined by using a Durrum D-500 automatic analyser as described previously (Conlon et al, 1987). Hydrolysis was carried out by using approx.…”
Section: Structural Analysismentioning
confidence: 99%